PEMBERDAYAAN KELOMPOK TERNAK SAPI BALI MELAUI TEKNOLOGI PENGOLAHAN PAKAN SILASE DAN PEMBUATAN PUPUK DI DESA SUSUPU KABUPATEN HALMAHERA BARAT - Nur Sjafani ,; Sri Lestari ,; M Ade Salim, (JURNAL PENGABDIAN MANDIRI, 2022)
Community Service Activities are a collaborative activity between the PKM team of the Faculty of Agriculture Unkhair and Partners, namely the FeedLot livestock group in Susupu Village, Sahu District, West Halmahera Regency. The problem with partners is that they do not know about feed processing technology. The purpose of this service is to build an independent farmer community, increase the knowledge of residents about how to make silage and synergize the potential of lecturers and students in carrying out community service. To achieve the goal of service, counseling and training in making silage are carried out. The activity was carried out in several stages, namely surveys, counseling and training and implementation. The results of service activities are that farmers respond very well, breeders can make silage and know the use of silage.